(untitled) (TAMADDUN NURI JURNALI, 2024)
The art of public speaking involves a complex interplay of linguistic and extralinguistic elements that are crucial for effective communication. Linguistic aspects encompass the choice of words, sentence structure, grammar, and overall coherence of the message. These elements are essential for conveying the speaker’s ideas clearly and effectively to the audience. Additionally, the tone, style, and register of language used play a significant role in engaging the listeners. Conversely, extralinguistic aspects encompass non-verbal components such as body language, facial expressions, gestures, posture, eye contact, and vocal delivery. These elements greatly influence how the audience perceives the speaker and the message being conveyed. For instance, maintaining eye contact can establish a connection with the audience, while appropriate gestures can enhance the impact of the spoken words.